2016
DOI: 10.15405/epsbs.2016.05.24
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Technology Education Development at Schools in Slovakia

Abstract: Between 2008 and 2013 Slovakia went through a curricular reform. The impact of the reform on technology education at lower level of secondary education was evaluated from 2013 to 2015. The need to reinforce some qualitative aspects of this analysis led in 2015 to a decision to carry out an additional research based on a personal inquiry, particularly on focus group interviews. The aim of the additional research was to find out how the teachers teaching the subject Technology (which before the curricular reform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In 2013, Boutou confirms that future professionals must be prepared from the perspective of sustainability to be competitive and be http://dx.doi.org/10.15405/epsbs.2017.01.02.27 Corresponding Author: Larisa Ivascu Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 261 hired easily by companies. In the studies Godemann et al (2014), Amaral et al (2015), and Haskova et al (2016) it is shown the important role that sustainable development plays in the curriculum of the students.…”
Section: Problem Statementmentioning
confidence: 99%
“…In 2013, Boutou confirms that future professionals must be prepared from the perspective of sustainability to be competitive and be http://dx.doi.org/10.15405/epsbs.2017.01.02.27 Corresponding Author: Larisa Ivascu Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 261 hired easily by companies. In the studies Godemann et al (2014), Amaral et al (2015), and Haskova et al (2016) it is shown the important role that sustainable development plays in the curriculum of the students.…”
Section: Problem Statementmentioning
confidence: 99%